179 To Scan or Not to Scan: The Role of Follow-up CT Scanning for Management of Chronic Subdural Hematoma After Neurosurgical Evacuation (TOSCAN) a Randomized, Controlled Trial. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Schucht, Philippe; Fischer, Urs; Fung, Christian; Bernasconi, Corrado; Fichtner, Jens; Vulcu, Sonja; Schöni, Daniel; Nowacki, Andreas; Wanderer, Stefan; Eisenring, Christian; Jetzer, Anna-Katharina; Soell, Nicole; et al.
Abstract: INTRODUCTION: Chronic subdural hematoma has a high recurrence rate after surgery and postoperative scans often show substantial residuals, eventually leading to a higher rate of reoperation. However, the benefit of postsurgical imaging for patient outcome remains unknown. METHODS: We randomly assigned 368 patients with newly diagnosed chronic subdural hematoma within 48 h after surgery to either a combined radiological and clinical follow-up (CT arm) or a clinical follow-up with scans only in case of neurological deterioration (no-CT arm). The primary outcome was the modified Rankin scale (mRS) score at 90 d; this categorical scale measures functional outcome, with scores ranging from 0 (no symptoms) to 6 (death). RESULTS: A follow-up protocol with CT imaging did not improve the primary outcome; there was no significant between-arm difference for mRS as a categorical variable ( P  = .79) or as numerical variable ( P  = .37). The proportion of patients who survived without severe disability (mRS 0-3) was 89% in the CT arm and 93% in the no-CT arm (odds ratio 1.4, 95% confidence interval 3.72-0.82, P  = .15). Death occurred in 12 patients in the CT arm and in 8 patients in the no-CT arm ( P  = .5). Re-operation for recurrent hematomas was performed in 59 patients in the CT arm and in 39 patients in the no-CT arm ( P  = .055). Complications were seen in 26 patients in the CT arm and in 19 patients in the no-CT arm ( P  = .34). CONCLUSION: Routinely scheduled CT scans after neurosurgical evacuation of chronic subdural hematoma have no benefit on outcome.